Propuesta para establecer criterios para el manejo ambiental enfocados en conservar la calidad del agua superficial en la subcuenca del Río Rincón dentro de La Reserva Forestal Golfo Dulce en La Península de Osa - Robleto-Villalobos, Laura (Instituto Tecnológico de Costa Rica, 2018)
Watersheds in Costa Rica show a deterioration in their water quality, associated to the lack of an urban development planning to define the uses for each area. This planning absence leads to inadequate uses in areas of high ecological fragility. The use of a water quality predictive model based on socio-environmental variables allowed the evaluation of different scenarios and the impact of socio-environmental changes on water quality in the future, in the sub-basin of the Rincón River, an area selected as a sample within the Golfo Dulce Forest Reserve. The model used was developed by researchers at the ITCR and evaluates the quality of water by analyzing socio-environmental variables, such as population density and land use. According to the evaluation of scenarios, the increase of the uses for pastures or fallow land does not harm the quality of the water if kept below 25% of the total area. It was found that the increase in permanent plantings area and the loss of forest does affect the quality of the water negatively. It was also found that the decision criterion of greater weight for environmental management, oriented to preserve water quality as class 2, obeys to maintain the forest cover and to incentive economic activities that can coexist with the standing forest. In addition, it was determined that, through the development of relevant activities, a decent standard of living can be maintained for the residents of the RFGD, and at the same time preserve the water quality of their rivers, as an investment for their present and future. It was possible to establish criteria for environmental management focused on conserving the quality of surface water in the sub-basin of the Rincón River, to be replicated within the Golfo Dulce Forest Reserve in the Osa Peninsula.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2018
Keywords: Manejo; Calidad; Uso de suelo; Cuencas; Agua